ASPEK HUKUM TINDAK KEKERASAN TERHADAP PESERTA DIDIK OLEH PENDIDIK DALAM PERSPEKTIF HUKUM PIDANA DAN HUKUM PIDANA ISLAM - Kriswanto Kriswanto (LPPM Universitas Bina Bangsa, 2022)
Structural violence is systemic and invisible violence, but destructively breeds extreme, widespread and long-term poverty, death and suffering for children. Structural violence, often referred to as system abuse, can be corrupt practices, collusion and nepotism (KKN), repressive control, monopolistic and exploitative economic practices that harm the state, and in turn create socioeconomic conditions that give birth to and nourish the roots of poverty and social violence against children. One of the portraits of structural violence is child and woman trafficking. They are generally traded for employment in illegal and dangerous places, such as in wild mining, nightlife and prostitution. The problem of the lack of efficiency of various laws (uu) and presidential decrees (Keppres) is as a guarantor of the implementation of child protection assigned in the regulation has no role, and only revolves around cases and penalties, so that interested parties do not receive their rights reasonably. If it already exists then the authorities provide protection against cases of receiving child abuse treatment is actually implemented, then there is no longer any reason for the authorities to protect the party not to carry out its human obligations. This research is done by building a theory that refers to the provisions of the laws and regulations, the opinions of legal experts written in books or scientific journals of legal science. In the research, it also takes the opinion of practitioners, both those who are state apparatus, law enforcement and legal practitioners who are known to be consistently within the scope of criminal law. The research specification is descriptive analytical because the study will reveal and analyze the legal symptoms that exist at this time. In this study described various problems and facts related to reform and criminal law policy.